Compounds, compositions, and methods of agelastatin alkaloids: patent evaluation of WO2015042239 (A1). (1st February 2017) - Yoshimitsu, Takehiko; Tun, Han W.
ABSTRACT: Agelastatins are a family of tetracyclic alkaloids isolated from marine sponges. The patent examined in this publication covers the chemical synthesis of agelastatins A to F and eight analogues and their therapeutic use against hematologic malignancies. The claim on the chemical synthesis features a novel biomimetic cyclization of a tricyclic precursor, which streamlines scalable access to agelastatins and their analogues. This new synthetic approach can potentially expedite the research on these compounds for therapeutic use against cancers by making them more easily available. The claim on the therapeutic use against hematologic malignancies is based on the in vitro cytotoxicity against a limited number of cell lines and can be further strengthened by in vivo therapeutic evaluations focusing on specific hematologic malignancies. The comparative evaluation of the cytotoxicities of the natural alkaloids described in the application greatly enhances the understanding of their structure-activity relationships (SARs) relevant to the development of novel medicinal leads. Overall, the patent application is strong and has the potential to advance the rapidly expanding agelastatin research.